Clinical, radiographic, ultrasonographic diagnosis, and treatment of urolithiasis in two domestic cats - case report - Polat, Eren; Saglıyan, Aydın (Kastamonu Üniversitesi, 2022)
In this case report, clinical, radiographic, and ultrasonographic diagnosis, and operative treatment of uroliths encountered in the urinary bladder of two domestic cats were shared. In the radiographic and ultrasonographic examinations of both cats brought with complaints of intermittent urination, uroliths were detected in their urinary bladders. After the uroliths were removed by cystotomy operation, it was determined that both cats were followed for six months and were in good health and no recurrence was observed.
Keywords: Veterinary Surgery; Veteriner Cerrahi